THE ATTITUDES OF STAKEHOLDERS TO IRRIGATION WATER PRICING AND PAYMENT: GAP-HARRAN PLAIN SAMPLING-TURKEY - H. AYDOGDU, Mustafa; AYDOGDU, Murat (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2015)
Agricultural irrigations have water use by 72.7% in Turkey. Southeastern Anatolian Project, GAP, is an integrated regional development project, mainly based on water and soil resources, where Harran plain is located. Agricultural irrigation is managed by water user associations (WUA) that have structural problems. It is aimed to determine the attitudes of the stakeholders’ to irrigation water pricing and payment. The basic material comes from farmers, the chairman and the manager of WUAs and State Hydraulic Works, DSI, staffs that can be called as stakeholders. 470 questionnaires were conducted by face to face interviewed. Likert attitude scale is used. Positive attitudes towards to water charging is 54.8%, current water charges are found high by 35.6%. If the pricing will be based on volumetric, it is believed that farmers will be more careful and efficient in use of water by 66.8%. This study is first of its type in GAP-Harran plain.